Digital Resource Activation and Competitive Positioning in Indonesian MSMEs - Dudi Hendra Fachrudin; Cahyat Rohyana; Rahma Hanum (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study investigates the micro-level process through which system features are transformed into digital resources and activated through sensing, seizing, and reconfiguring capabilities to generate emerging competitive positioning in Indonesian MSMEs. Research Methodology: A multiple-case embedded design involving six Indonesian MSMEs was employed. Data were collected over six weeks through semi-structured interviews with twelve informants, participatory observation, and system log analysis. Data analysis followed within-case analysis, cross-case pattern matching, and analytical generalization stages. Results: Routine embedding and managerial decision commitment are decisive in determining whether digital artifacts acquire strategic value. Data utilization intensity stimulates sensing capability; however, without managerial commitment, sensing does not evolve into seizing. Organizational adjustment further determines the effectiveness of reconfiguring capability. MSMEs with high activation intensity exhibited clearer emerging competitive positioning, including improved customer retention and faster market response. Conclusions: Digital transformation in MSMEs operates as a staged activation continuum rather than a technology adoption event. Emerging competitive positioning arises only when resource qualification and capability activation align cumulatively. Digital investment alone does not guarantee competitive differentiation; behavioral institutionalization and managerial agency are essential. Limitations: The study is limited to six MSMEs in a single regional ecosystem, restricting statistical generalization. The observation period captures early-stage activation effects rather than sustained competitive advantage. Contributions: This study proposes a staged resource activation mechanism integrating RBV-oriented digital resource scholarship and dynamic capability theory within digitally emerging MSME contexts, offering theoretical refinement and practical guidance for policymakers and SME leaders in developing economies